Pulmonary Rehabilitation in Patients Recovering from COVID-19 - Zampogna, Elisabetta; Paneroni, Mara; Belli, Stefano; Aliani, Maria; Gandolfo, Alessandra; Visca, Dina; Bellanti, Maria Teresa; Ambrosino, Nicolino; Vitacca, Michele (Respiration, 2021)
Background: In hospitalized patients recovering from the SARS-coronavirus-2 disease 19 (COVID-19), high prevalence of muscle weakness and physical performance impairment has been observed. Objectives: The aim of this study was to evaluate the effectiveness of pulmonary rehabilitation in these subjects in a real-life setting. Methods: Retrospective data analysis of patients recovering from COVID-19, including those requiring assisted ventilation or oxygen therapy, consecutively admitted to an in-patient pulmonary rehabilitation program between April 1 and August 15, 2020. Short Physical Performance Battery (SPPB: primary outcome), Barthel Index (BI), and six-min walking distance were assessed as outcome measures. Results: Data of 140 patients were analyzed. After rehabilitation, patients showed improvements in SPPB {from: (median [IQR]) 0.5 (0–7) to 7 (4–10), p < 0.001} and BI (from 55 [30–90] to 95 [65–100], p < 0.001), as well as in other assessed outcome measures. The proportion of patients unable at admission to stand, rise from a chair and walk was significantly reduced (p < 0.00). Conclusions: Pulmonary rehabilitation is possible and effective in patients recovering from COVID-19. Our findings may be useful to guide clinicians taking care of patients surviving COVID-19 infection.